2014
DOI: 10.1080/10937404.2014.884956
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Chemical Concentrations in Maternal and Cord Blood: A Review of Available Data

Abstract: The developing fetus is likely to be exposed to the same environmental chemicals as the mother during critical periods of growth and development. The degree of maternal-fetal transfer of chemical compounds will be affected by chemical and physical properties such as lipophilicity, protein binding, and active transport mechanisms that influence absorption and distribution in maternal tissues. However, these transfer processes are not fully understood for most environmental chemicals. This review summarizes repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 133 publications
6
64
0
Order By: Relevance
“…However, certain pesticides that may have been used in tea production, such as OC pesticides -including p,p′-dichlorodiphenyldichloroethylene (p,p ′-DDE) and hexachlorobenzene (HCB) -and OP pesticides, have been shown to cross the blood-placenta barrier, and thus may put the fetus at risk (Aylward et al, 2014). For example, maternal exposure to HCB has been associated with an increased risk of preterm birth (PTB).…”
Section: Introductionmentioning
confidence: 99%
“…However, certain pesticides that may have been used in tea production, such as OC pesticides -including p,p′-dichlorodiphenyldichloroethylene (p,p ′-DDE) and hexachlorobenzene (HCB) -and OP pesticides, have been shown to cross the blood-placenta barrier, and thus may put the fetus at risk (Aylward et al, 2014). For example, maternal exposure to HCB has been associated with an increased risk of preterm birth (PTB).…”
Section: Introductionmentioning
confidence: 99%
“…One aspect to be considered in this comparison of OC concentrations at different ages is the lower lipid content in cord blood serum compared to venous serum (Aylward et al, 2014;Vizcaino et al, 2014). The average lipid content in cord blood and the 4 years serum samples of the Menorca children is 2.6 and 8.2 g/L, respectively (Carrizo et al, 2007a), and the average lipid concentrations in the 14 years serum samples is 5.2 g/L.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…p,p′ -DDT/E have been shown to transfer to children during pregnancy (Aylward et al, 2014) and breastfeeding (LaKind et al, 2009), resulting in exposures during critical windows of development. Multiple studies have provided evidence of the substantial impact of breastfeeding on children’s p,p′ -DDE levels.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have provided evidence of the substantial impact of breastfeeding on children’s p,p′ -DDE levels. Whereas neonates’ serum p,p′ -DDT/E levels are similar or slightly lower than maternal levels at birth on a lipid basis (Aylward et al, 2014), studies with longitudinal measurements have shown that children’s serum levels can increase substantially during breastfeeding (Lackmann, 2006). Studies have reported that breastfed children have higher p,p′ -DDE levels than children who had been fed formula, from as early as 6 weeks of age (Lackmann et al, 2004) to as late as 14 years (Gascon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%